2012
DOI: 10.4103/0970-1591.105749
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of complications using the modified Clavien grading system, and of success rates of percutaneous nephrolithotomy using Guy′s Stone Score: A single-center experience

Abstract: Introduction and Objectives:To prospectively document the perioperative complications of percutaneous nephrolithotomy (PCNL) using the modified Clavien grading system. Evaluation of complications and clearance rates according to stone complexity using the validated Guy's Stone Score (GSS) was also done.Materials and Methods:A total of 221 renal units underwent 278 PCNL procedures at a urology resident training center between September 2010 and September 2011 and data were recorded prospectively in our registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 31 publications
4
32
0
1
Order By: Relevance
“…In two different studies conducting external validation of the Guy scoring system, Mandal and Ingirmasson evaluated this scoring system as an efficient instrument in predicting the stone-free status [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two different studies conducting external validation of the Guy scoring system, Mandal and Ingirmasson evaluated this scoring system as an efficient instrument in predicting the stone-free status [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their series involving 278 PCNL cases, Mandal et al observed that the stone-free rates decreased as 100%, 74%, 56%, and 0% according to the GS 1, 2, 3, 4 scores respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This classification system has been used for grading complications in oncological procedures such as radical cystourethrectomy[ 12 ] and radical prostatectomy;[ 13 ] laparoscopic procedures such as pyeloplasty[ 14 ] and live donor nephrectomy;[ 15 ] endourological procedures such as transurethral resection of prostate,[ 16 ] percutaneous nephrolithotomy,[ 17 ] and semi-rigid ureteroscopy. [ 18 ] However, the modified CCS has been less frequently used for TURBT.…”
Section: Introductionmentioning
confidence: 99%
“…At the current time, the Guy's Stone Scoring (GSS) system [37], the STONE nephrolithometry scoring system [8, 9], and the CROES (Clinical Research Office of Endourological Society) nomogram [10] are used for the prediction of the success rate and possible complications following PCNL in research and clinical practice. Previous studies reported that the Guy's stone score is significantly associated with stone-free status [37]; however other studies reported an association of this score with complications [4, 6]. STONE nephrometric scores were significantly associated with stone free status but not with postoperative complications [8, 9].…”
Section: Introductionmentioning
confidence: 99%